Is Holmium Laser an Appropriate Modality to Treat Genital Warts? - Ghiasy, Saleh; Fallah-Karkan, Morteza; Razzaghi, Mohammad Reza; Ranjbar, Arash; Rahavian, Amirhosein; Javanmard, Babak (Journal of Lasers in Medical Sciences, 2018)
Introduction: Genital warts in young adults aged 18-28 years are very common. Several approaches are routinely used in the treatment of warts, viz., medical treatment (podophyllin and trichloroacetic acid), conventional surgery (excision or electrocautery), cryotherapy, and laser treatment. Because of high recurrence rates after treatment, complications and long duration of treatment, newer modalities have been developed. One of these newer methods is laser, which has been used in several urologic diseases. However, there are only a few studies about use of Holmium laser for treatment of genital warts. This retrospective study compared the success rate of Holmium laser with other available treatments for genital warts. Methods: Between October 2011 and May 2016, 142 patients with genital warts attended the urology clinics at Shohada-e-Tajrish hospital in Tehran, Iran. Out of these, a total of 101 patients were included in this study consisting of 42, 39, 11 and 9 patients treated with cryotherapy, laser, conventional surgery and podophyllin respectively. Results: The most successfully cleared lesions were seen in the holmium laser treatment group (P = 0.001). The lowest recurrence rate was observed in the holmium laser treatment group (P = 0.001). 17 patients had one of these following problems: dysuria, initial hematuria or a change in the force and caliber of their urinary stream that after physical examination showed them to have a meatal wart. These patients then underwent cystoscopy up to urinary sphincter. All of them in addition to the meatus wart had a penile shaft lesion(s). Thirteen patients had meatal lesions, 9 of whom received holmium laser therapy and 4 patients were treated with electrocautery. Based on routine follow up after treatment, none of the patients treated with holmium laser had urinary stricture, but one case treated with electrocautery returned with a penile urethral stricture. Conclusion: This study showed that treatment with Holmium laser has the highest clearance rate (92.2%) and lowest recurrence rate (14.3%) compared to other available treatments in this study. It may be concluded that holmium laser is a safe and effective treatment for genital warts with a low rate of recurrence.